Prospective study feasibility: Screening of antenatal total abnormal pulmonary venous return. (11th January 2018) - Levêque, Christine; Paret, Louise; Cochet, Tiffany; Joinau‐Zoulovits, Félicia; Chantalat, E.; Vidal, F.; Vayssière, Christophe; David, Nadine
Abstract: Introduction: Total abnormal pulmonary venous return is a heart defect often missed prenatally, yet at birth, it is a surgical emergency. Antenatal detection could be improved by sonographic visualization of the anastomosis of 2 pulmonary veins in a sinus into the left atrium. The objective of this study is to evaluate the feasibility of this screening method. Method: Prospective observational study. Five operators selected one representative image taken during morphological ultrasound screening. Anonymized images were later assessed for quality by an expert. Both the operator and the expert were asked to rate the picture and collect clinical data. Feasibility corresponded to the percentage of images judged satisfactory by the expert; reliability corresponded to the percentage judged satisfactory by both the expert and the sonographer. Results: A total of 192 patients were included. Feasibility was 73% (95% confidence interval, 67.1%‐79.7%) and reliability was 81.4% (95% confidence interval, 75.9%‐86.9%). There was no learning curve. Conclusion: This study confirms that visualization of the 2 pulmonary veins in a sinus into the left atrium at midtrimester screening is simple and reproducible. The next stage is to evaluate the sensitivity and specificity as a screening test of total abnormal pulmonary venous return and whether that would improve morbidity and mortality.